UK Sport Talent Identification & Development (2012)
The UK Talent Team is a collaboration between UK Sport and the English Institute of Sport (EIS). It supports World Class Programmes to identify and develop talented athletes and the construction of the underpinning support systems. Funded as part of UK Sport`s eight year strategic investment into development, the UK Talent Team`s work focuses on the 714 development (Podium Potential) athletes, and their coaches and managers who have the capacity to impact on future Olympic and Paralympic games.